The smoke of the soul: medicine, physiology and religion in Early Modern England - Sugg, Richard (Palgrave Macmillan, 2013)
"What was the soul? For hundreds of years Christians agreed that it was the essential, immortal core of each individual believer, and of the Christian faith in general. Despite this, there was no agreement on where the soul was, what it was, or how it could be joined to the material body. By focusing on the spirits of blood which were alleged to join body and soul, this book explores the peculiar problems, anxieties, and excitement generated by a zone where spirit met matter, and the earthly the divine. It shows how pious but rigorous Christians such as John Donne and Walter Raleigh expressed their dissatisfaction with existing theories of body-soul integration; how prone the soul was to being materialised; and how an increasingly scientific medical culture hunted the material aspects of the soul out of the human body"--